XRD Peak Profile Analysis of SiC Reinforced Al2O3 Ceramic Composite Synthesized by Electrical Resistance Heating and Microwave Sintering: A Comparison. (4th August 2021) - Mohankumar, Madhan; Praveen Kumar, S.; Guruprasad, B.; Manavalla, Sreekanth; Isaac JoshuaRamesh Lalvani, Joshua Stephen Chellakumar; Somasundaram, P. L.; Tamilarasu, P.; Tanwar, Prakash Singh
Abstract : Al2 O3 with 10 wt.% of SiC ceramic composite is synthesized at 1500°C by electrical resistance heating sintering with a holding time of 5 hours and microwave sintering methods with a holding time of 15 minutes. The samples generated by the two methods are characterized using powder X-ray diffraction and field emission scanning electron microscopy (FESEM). Experiments with both samples showed that the existence of the α -Al2 O3 and β -SiC phases in both samples was verified by the findings of XRD pattern on both samples. Microstructure study illustrates that the Al2 O3 matrix particles have spherical-like shape and their average matrix particle size is 67 ± 5 nm for electrical resistance heating sintered sample and 38 ± 5 nm for microwave sintered sample. The lattice strain and crystallite size of Al2 O3 matrix were measured using Williamson–Hall (W-H) methods, which were achieved via the use of XRD peak broadening, based on a diffraction pattern. Three modified W-H models were used to compute other parameters, including strain ( ε ) and stress ( σ ), as well as energy density ( u ). These models were the uniform deformation model (UDM), the uniform deformation energy density model (UDEDM), and the uniform deformation stress model (UDSM). The average crystallite sizes of α -Al2 O3 attained from these three models of Williamson–Hall (W–H) methods and FESEM analysis are correlated and found very close to each other. In all three models of the W-H technique, X-ray diffraction peak profile examination of electrical resistance heating-sintered and microwave-sintered Al2 O3 /10 wt. % SiC ceramic composite reveals that the microwave-sintered sample has finer crystallite size with less strain.